Gaya Kepemimpinan Gubernur DKI Jakarta Berdasarkan Prinsip Tata Kelola Kepemerintahan Yang Baik (GCG) - Sulistyo Seti Utami (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
When Joko widodo was elected as a governor of DKI Jakarta, it has proven that today's people are more realistic and smarter to choose their leader for period 2012-2017, even though at that time a lot of issue of syara, personality, being raised, but people keep choose Joko VVi dodo and Ahok who are able bring changes to DKI Jakarta. After one year Joko VVi dodo sit as a governor, people has been able to feel that his work programs are pro-people, almost every day he goes to see slums, relocate many markets or places into the correct functions, such as Tanah Abang market. His Success as a solo governor and DKI Governor Jakarta (even still only one year), based on the results of the survey showed that Joko VVi dodo is in the first place as a candidate for President of the Republic of Indonesia in 2014. Joko VVi dodo understand well what exactly needed by the community Indonesia at this moment, he is the leader figure expected by Indonesian people. His leadership style is low profile, not much to say but a lot of work, and discipline. Joko VVi dodo's leadership is based on the concept of good corporate governance, which consists of Participation, rule of law, transparency, responsiveness, consensus orientation, equity, efficiency, effectiveness, accountability, having strategic vision.